The Use of Wordwall Applications in Islamic Religious Learning for Children with Special Needs at SLB Kokalukuna - Sindi, Sindi; Rusli, Rusli; Ridwan, Muhammad (Journal of English Language and Education, 2025)
This study aims to examine the effectiveness of using the Wordwall application in Islamic Religious Education (PAI) for children with special needs, particularly deaf students at SLB Kokalukuna. The research is based on the need for engaging and adaptive learning media that meets the specific learning needs of students with disabilities. This research uses a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, and questionnaires distributed to students. The results show that Wordwall is highly favored by students in Islamic studies classes. 100% of the participants stated that the application is interesting and suits their learning needs due to its visual and interactive nature. Furthermore, 80% of the students expressed willingness to continue using Wordwall in future learning, while 20% faced challenges due to limited technological facilities. The study concludes that Wordwall is an effective and inclusive learning tool for children with special needs, provided it is supported by adequate infrastructure.